PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK BERBASIS MODEL KOOPERATIF TEAM ASSISTED INDIVIDUALIZATION PADA MATERI KOORDINAT KARTESIUS SMP KELAS VIII - Tesha Widya Jayu (Departemen Matematika, 2020)
The purpose of this research is to develop learning tools in the form of Student Worksheets (LKPD) based on the cooperative model Team Assisted Individualization that is valid and practical on Cartesian coordinate material for grade VIII junior high school students. This research is a development research by modifying the Plomp development model which consists of three phases, namely preliminary research, prototyping stage, and the assessment phase. Based on the results of the validity data analysis, it shows that LKPD based on thecooperative model Team Assisted Individualization from the aspect of content feasibility, cooperative model Team Assisted Individualization, language, presentation and graphics have a validity level of 89.2% with a very valid category. LKPD also met the practical criteria from the results of the questionnaire responses of three students who had carried out the One to One Evaluation with a percentage of 90.19%. Based on these results, it can be concluded that the LKPD based on the cooperative model Team Assisted Individualization on Cartesian coordinate material for grade VIII junior high school students can be declared valid and practical. Keywords, Development Research, Student Worksheet, Team Assisted Individualization